2000
DOI: 10.1029/1999jd900753
|View full text |Cite
|
Sign up to set email alerts
|

NOy lifetimes and O3 production efficiencies in urban and power plant plumes: Analysis of field data

Abstract: Abstract. In an effort to describe and characterize power plant plumes in the Nashville region, emissions from a small power plant (Gallatin) and a large power plant (Paradise) were examined using data obtained on the Department of Energy G-1 airborne sampling platform. Observations made on July 3, 7, 15, 17, and 18, 1995, were compiled, and a kinetic analysis of the chemical evolution of the power plant plumes was performed. Analysis of the power plant plume data revealed a very active photochemistry, as had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 34 publications
5
70
0
Order By: Relevance
“…Of particular concern is depletion of NOy due to dry deposition, which will increase the value of CO/NOv as was sometimes observed to happen in the Nashville, Tennessee urban and power plant plumes [Gillani et al, 1998a;Nunnermacker et al, 1998Nunnermacker et al, , 2000. The use of a regression method partially eliminates that concern as the regression slope is only sensitive to increases above background and is therefore not affected by deposition of background NOy.…”
Section: Co/no R the Ratio Co/noy Provides A Useful Test Of Anmentioning
confidence: 99%
“…Of particular concern is depletion of NOy due to dry deposition, which will increase the value of CO/NOv as was sometimes observed to happen in the Nashville, Tennessee urban and power plant plumes [Gillani et al, 1998a;Nunnermacker et al, 1998Nunnermacker et al, , 2000. The use of a regression method partially eliminates that concern as the regression slope is only sensitive to increases above background and is therefore not affected by deposition of background NOy.…”
Section: Co/no R the Ratio Co/noy Provides A Useful Test Of Anmentioning
confidence: 99%
“…From a pollution point of view, all regions are similar to the conditions encountered over the Swiss Plateau. For an assumed temperature of 298 K and based on OH concentrations taken from the BERLIOZ and the SLOPE96 campaigns with noontime values of (4-8)×10 6 cm −3 (Volz- Mihelcic et al, 2003) and (7-10)×10 6 cm −3 (Volz-Thomas and Kolahgar, 2000), respectively, the resulting mean daytime NO x lifetimes in summer are estimated to be 4.6 h and 3.0 h. These data have been deduced from campaigns in the U.S. (Spicer, 1982;Ryerson et al, 1998;Nunnermacker et al, 2000;Sillman, 2000) and in the Swiss Plateau (Dommen et al, 1999), from GOME NO 2 VTCs over Germany (Beirle et al, 2003) and from the GEOS-CHEM model (Fig. 7).…”
Section: No X Lifetime Under Anticyclonic Clear Sky Conditionsmentioning
confidence: 99%
“…The seasonal mean lifetimes are summarised in Table 1 -from measurements in urban plumes: Boston: 5.5 h (Spicer, 1982), Nashville: 2.0 h (Nunnermacker et al, 2000), Zurich: 3.2 h (Dommen et al, 1999),…”
Section: No X Lifetime Under Anticyclonic Clear Sky Conditionsmentioning
confidence: 99%
“…Neuman et al (2009) reported the lifetime of HNO 3 to dry deposition was 14 hours in Houston. Nunnermacker et al (2000) calculated an NO z lifetime in the Nashville urban plume of 8.7 hours, although they acknowledge that this short lifetime would correspond to an unexpectedly fast deposition velocity 30 of 6.7 cm s -1 for HNO 3 . In a pine forest environment, Farmer and Cohen (2008) calculated a deposition velocity of HNO 3 of 3.4 cm s -1 .…”
Section: The Lifetimes Of No Yimentioning
confidence: 99%